3c-c=12

Simple and best practice solution for 3c-c=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3c-c=12 equation:


Simplifying
3c + -1c = 12

Combine like terms: 3c + -1c = 2c
2c = 12

Solving
2c = 12

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '2'.
c = 6

Simplifying
c = 6

See similar equations:

| 12+1/2h=15+2/3h | | 6/x-4/x=5/8 | | 60/90=x/50 | | 4qr+9t=7u | | 7z-z=-3+3-2-4 | | -2(5-x)=10 | | -7(8-8n)=-168 | | -12n+10=-10n-12 | | 24.84-22.7= | | -2(4t-4)+6t=5t-4 | | 7/9=1/3b | | X-83=-100 | | 7-3(w-3)=23+2(3w+1) | | 96=-8(x-4) | | 2x-15+x+55=360 | | 2x-15+x+55=90 | | -31=22-x | | 0.11y+0.07(y+2000)=860 | | 2r+r=12 | | 12-1/2h=15-2/3h | | 2(-3-v)-3v(1-6v)= | | 36-10x=20+6x | | 7z-2=-3+3z-2-4 | | 7z-2=-3 | | 5x-2+x=x-3+5x | | -4x-6=-3x+7 | | 3x+5x-8=2(8+x) | | -3(x+1)=-18 | | 7(z-12)=3(z-13) | | 7n-1=64-8n | | 6-(3x+5)=9x-3(4x+1)+2 | | 6-9x=6x-10x-9 |

Equations solver categories